ANALYSIS OF CUSTOMER DECISION PREFERENCES ON GLOD COLLATERAL LOANS AT BANK MANDIRI MITRA SYARIAH - Imaroh, Ikhda Maslikhatul; Setiawan, Firman (I-Finance Journal, 2024)
This quantitative research aims to identify factors that influence customers' decisions in choosing gold collateral services at Bank Mitra Syariah. The population of this study was 4,947 customers on gold collateral loans at sharia partner banks. The sample size used in the research was 370 customers who were selected using a purposive sampling method with the criteria being that the respondent was at least 17 years old and had a gold collateral loan. Data was collected using a questionnaire containing questions related to variables on a Likert scale, and processed using SPSS version 25 software. The results of the analysis showed that the variables promotion, ijarah fees, late fines, place and service quality had a positive and significant influence on customer decisions. On the other hand, the estimated value variable shows a positive and insignificant influence on customer decisions. The conclusion is that the factors that influence customer decisions, namely promotions, ijarah fees, late fines, location and service quality, are the main drivers in customers' decisions to choose gold collateral loans, while the estimated value has no effect on sustainable gold collateral loans.